A modified aerogel powder and preparation method and application thereof
By introducing polyaniline coated nickel oxide and aminolated carbon nanotubes into polyimide aerogel, a polymer-based electromagnetic shielding composite material with a multiphase structure is solved, and the problem of low electromagnetic shielding performance of 3D printed polyurethane materials is solved. Significantly improves electromagnetic shielding performance and mechanical properties.
Patent Information
- Application Number
- CN202411158135.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-22
AI Technical Summary
The electromagnetic shielding performance of 3D printed polyurethane materials is low, resulting in serious electromagnetic interference problems, affecting the normal use of equipment and human health.
Using modified aerogel powder, polyaniline-coated nickel oxide and aminolated carbon nanotubes are introduced into polyimide aerogel to construct a polymer-based electromagnetic shielding composite material with a multiphase structure to improve electromagnetic shielding performance. .
It significantly improves the electromagnetic shielding performance of 3D printed polyurethane materials, reduces secondary pollution of reflected waves, enhances absorption losses, optimizes the conductivity and compatibility of the materials, and solves the electromagnetic interference problem.
Smart Images

Figure CN118667223B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer gels, and in particular relates to a modified aerogel powder, a preparation method and applications thereof. Background Art
[0002] Since the beginning of the 21st century, 3D printing technology has been vigorously developed and has initially formed a certain scale of industrialization, including in aerospace, vehicle engineering, civil life and other aspects. 3D printing technology, also known as additive manufacturing, is an advanced processing method that integrates many disciplines such as materials science, control engineering, and digital modeling, and can be directly and quickly formed. Compared with traditional processing methods, 3D printing technology is a technical supplement to traditional processing methods, which avoids the restriction that traditional processing methods must rely on molds to form product structures. The unique advantage of 3D printing technology is that it can directly and quickly form products, and can ensure the complex surface structure and internal structure of the molded products, effectively avoiding the technical deficiencies caused by the difficulty of molding and demolding of complex structures in traditional molding, and increasing the diversity of product structure design.
[0003] In recent years, with the widespread application of various 3D printing technologies in various fields, the types of 3D printing raw materials have also increased. Polyurethane materials are widely used in 3D printing of various parts because of their excellent performance and great adjustability of hardness, strength, melting temperature and other properties. At present, with the rapid development of 3D printing technology, the huge difference in performance between 3D printing parts and traditional mold processing parts has become an important factor restricting its wider application. The performance of 3D printing parts is mainly determined by factors such as the 3D printing equipment itself, 3D printing materials, and the setting of process parameters during 3D printing. Among these influencing factors, 3D printing materials are one of the most important ones. With the continuous advancement of 3D printing polyurethane material technology, the performance of polyurethane material 3D printing products is getting better and better. At the same time, because 3D printing technology avoids mold manufacturing, 3D printing of products can be directly carried out, which greatly increases the diversity of product structure design. Therefore, the application of 3D printing of polyurethane materials in various fields continues to expand.
[0004] Especially in the field of highly integrated electronic components, polyurethane is more widely used. However, the high-frequency electromagnetic waves radiated between adjacent devices will interact with each other to cause electromagnetic interference, affecting the normal use of surrounding equipment, and even have a negative impact on human health, leading to the occurrence of complex diseases. Therefore, in order to suppress electromagnetic interference and improve the electromagnetic compatibility of equipment, it is of great significance to prepare 3D printed polyurethane materials with electromagnetic shielding properties on a large scale and in a green way. Summary of the invention
[0005] The purpose of the present invention is to provide a modified aerogel powder, which can solve the technical problem of low electromagnetic shielding efficiency of current 3D printing polyurethane materials. At the same time, the technology of the present invention can realize low-energy consumption and high-efficiency automated production.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing modified aerogel powder comprises the following steps:
[0008] (1) dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 0-5°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and after the addition is completed, continuing to stir for 10-24 hours to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles;
[0009] (2) Dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain a modified polyamic acid powder; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:(0.4-0.6);
[0010] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelization;
[0011] (4) adding the aminated carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the aminated carbon nanotubes is 1:(0.1-0.6);
[0012] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0013] The electromagnetic shielding mechanism of electromagnetic shielding materials includes reflection loss on the surface of the shielding body, absorption loss of the shielding material and multiple reflection loss inside the shielding body, while absorption loss includes dielectric loss and magnetic loss, and its magnitude depends on the dielectric constant and magnetic permeability of the shielding material. In order to give full play to the reflection loss and absorption loss of the shielding material. The present invention introduces polyaniline-coated nickel oxide and amino-modified carbon nanotubes into polyimide aerogel powder to construct a polymer-based electromagnetic shielding composite material with a multiphase structure, thereby improving the electromagnetic shielding performance of 3D printed polyurethane materials.
[0014] Polyimide aerogel has a honeycomb structure, which is not only light in weight and low in density, but also has many holes on the surface, which greatly reduces the secondary pollution caused by reflected waves and reflected electromagnetic waves. Multiple reflections between holes increase absorption loss and have excellent electromagnetic shielding performance. Nano nickel oxide has excellent electromagnetic shielding performance and can effectively absorb and reflect electromagnetic waves. However, nano nickel oxide belongs to inorganic materials. Although it has good magnetic properties, it has low electrical conductivity and poor compatibility with organic polymers. In order to solve this problem, the present invention uses polyaniline to coat and modify it, and then prepares polyamic acid by in-situ polymerization with polyimide monomer, thereby improving the adhesion ability of polyimide to nano nickel oxide and the electrical conductivity of nickel oxide. Moreover, polyaniline itself is an excellent conductive polymer, which can form a conductive network with carbon nanotubes on the surface of the gel, thereby improving the electromagnetic shielding performance of the modified aerogel powder. The prior art generally modifies the surface of carbon nanotubes by polymer coating, reduces the surface energy of carbon nanotubes, and improves the dispersion effect of carbon nanotubes in the polymer matrix. Although coating can solve the dispersion effect of carbon nanotubes in the polymer matrix and improve the electromagnetic shielding performance of the composite material, the coating modification often involves cumbersome steps, which limits its large-scale application in the industrial field. The present invention directly uses amino carbon nanotubes as electromagnetic shielding materials with conductive properties, adds amino carbon nanotubes to polyamic acid hydrogels, and in the subsequent thermal imidization process, the amino (-NH2) active groups on the surface of the amino carbon nanotubes will react with the carboxyl groups on the polyamic acid to graft the carbon nanotubes onto the polyimide. As a result, the modified aerogel powder matrix prepared by the present invention is a polyimide aerogel, and the interior of the aerogel is filled with polyaniline-coated nano nickel oxide particles, which solves the technical problems of low conductivity and poor compatibility of nickel oxide, and can play the role of reflection loss and absorption loss; and the surface of the aerogel is dispersed with curled fiber-shaped carbon nanotubes, which have multiple reflection loss effects. That is, the structure of the present invention gives full play to the reflection loss, absorption loss of each component and the multiple reflection loss inside and on the surface of the shielding material. The modified aerogel powder can be directly used as an electromagnetic shielding agent for 3D printed polyurethane materials. It does not have the compatibility problem of general fillers and does not require filler modification. It greatly increases the filling amount of the electromagnetic shielding agent and improves the electromagnetic shielding performance of the 3D printed polyurethane material.
[0015] Furthermore, in step (1), the particle size of the nickel oxide nanoparticles is 40-100 nm.
[0016] Furthermore, in step (1), the mass ratio of nickel oxide nanoparticles to aniline monomer is 1:(0.4-0.8); and the molar ratio of ammonium persulfate to aniline monomer in the ammonium persulfate aqueous solution is (0.5-1):1.
[0017] Furthermore, in step (2), the dianhydride monomer is selected from at least one of pyromellitic dianhydride, 3,3`,4,4`-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, and hexafluoro dianhydride; and the diamine monomer is selected from at least one of 4,4`-diaminodiphenyl ether, p-phenylenediamine, and 4,4'-diaminodiphenylmethane.
[0018] Furthermore, in step (2), the molar ratio of the dianhydride monomer to the diamine monomer is 1:(0.95-1.05); and the organic solvent is selected from at least one of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide.
[0019] Furthermore, in step (3), the organic base is at least one of triethylamine, tripropylamine, quinoline and triethylenediamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:(0.3-0.7).
[0020] Furthermore, in step (4), the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the amino carbon nanotube is 1:(0.2-0.4). Carbon nanotubes, as an external modifier for aerogels, not only improve the compatibility of aerogels with polyurethane, but also play a role in conducting electricity and taking into account multiple reflections. Within the above range, the conductive and shielding effects of the amino carbon nanotubes can be fully exerted, and the polyurethane resin will not be hindered from infiltrating the aerogel during the printing process, and the mechanical properties are excellent.
[0021] The present invention also provides an application of the modified aerogel powder, and the modified aerogel powder is used in the field of 3D printing polyurethane materials.
[0022] The present invention also provides a 3D printing polyurethane material, comprising the following components in parts by weight:
[0023] 100 parts of thermoplastic polyurethane elastomer; 10-20 parts of electromagnetic shielding aid; 1-3 parts of lubricant; the electromagnetic shielding aid is the above-mentioned modified aerogel powder.
[0024] Beneficial effects: The present invention introduces polyaniline-coated nickel oxide and amino-modified carbon nanotubes into polyimide aerogel powder to construct a polymer-based electromagnetic shielding composite material with a multiphase structure, thereby improving the electromagnetic shielding performance. The polyimide aerogel has a honeycomb structure, which is not only light in weight and low in density, but also has multiple holes on the surface, which greatly reduces the secondary pollution caused by reflected waves and reflected electromagnetic waves. Multiple reflections between holes increase the absorption loss, and the electromagnetic shielding performance is excellent. The interior of the aerogel is filled with polyaniline-coated nano-nickel oxide particles, which can play the role of reflection loss and absorption loss; and the surface of the aerogel is dispersed with curled fibrous carbon nanotubes, which have the effect of multiple reflection losses. The modified aerogel powder can be directly used as an electromagnetic shielding aid for 3D printed polyurethane materials. It does not have the compatibility problem of general fillers, and does not require filler modification. It greatly increases the filling amount of the electromagnetic shielding aid and improves the electromagnetic shielding performance of 3D printed polyurethane materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron micrograph of polyaniline-modified nickel oxide nanoparticles prepared in Example 7;
[0026] Figure 2 This is a transmission electron microscopy image of polyaniline-modified nickel oxide nanoparticles prepared in Example 7;
[0027] Figure 3 This is a graph of the X-band electromagnetic shielding performance of the 3D printed polyurethane material prepared in Examples 1-5;
[0028] Figure 4 This is a graph of the X-band electromagnetic shielding performance of the 3D printed polyurethane material prepared in Examples 6-9;
[0029] Figure 5 This is a graph of the X-band electromagnetic shielding performance of the 3D printed polyurethane material prepared in Comparative Examples 1-4. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and part will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0031] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0032] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.
[0033] The indefinite articles "a" and "an" before the elements or components of the present invention do not limit the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0034] In addition, the descriptions of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0035] Example 1
[0036] A method for preparing modified aerogel powder comprises the following steps:
[0037] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 0°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 10 hours after the addition is completed, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.4; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 0.5:1;
[0038] (2) Dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation reaction to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain modified polyamic acid powder; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:0.4; the dianhydride monomer is selected from pyromellitic dianhydride; the diamine monomer is selected from 4,4'-diaminodiphenyl ether; the molar ratio of the dianhydride monomer to the diamine monomer is 1:0.95; and the organic solvent is selected from dimethylacetamide;
[0039] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.3;
[0040] (4) adding the amino carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the amino carbon nanotubes is 1:0.2;
[0041] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0042] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 15 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0043] Example 2
[0044] A method for preparing modified aerogel powder comprises the following steps:
[0045] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 5°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 24 hours after the addition is complete, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.8; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 1:1;
[0046] (2) Dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation reaction to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain modified polyamic acid powder; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:0.6; the dianhydride monomer is selected from 3,3',4,4'-biphenyltetracarboxylic dianhydride; the diamine monomer is selected from 4,4'-diaminodiphenylmethane; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1.05; and the organic solvent is selected from dimethylacetamide;
[0047] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.7;
[0048] (4) adding the amino carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the amino carbon nanotubes is 1:0.4;
[0049] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0050] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 15 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0051] Example 3
[0052] A method for preparing modified aerogel powder comprises the following steps:
[0053] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 0°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 24 hours after the addition is complete, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.8; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 1:1;
[0054] (2) Dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation reaction to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain modified polyamic acid powder; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:0.6; the dianhydride monomer is selected from 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride; the diamine monomer is selected from 4,4'-diaminodiphenyl ether; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1; and the organic solvent is selected from dimethylacetamide;
[0055] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.4;
[0056] (4) adding the amino carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the amino carbon nanotubes is 1:0.2;
[0057] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0058] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 16 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0059] Example 4
[0060] A method for preparing modified aerogel powder comprises the following steps:
[0061] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 5°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 10 hours after the addition is completed, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.7; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 0.6:1;
[0062] (2) Dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation reaction to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain modified polyamic acid powder; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:0.4; the dianhydride monomer is selected from hexafluorodianhydride; the diamine monomer is selected from 4,4'-diaminodiphenyl ether; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1.01; and the organic solvent is selected from dimethylacetamide;
[0063] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.6;
[0064] (4) adding the amino carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the amino carbon nanotubes is 1:0.4;
[0065] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0066] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 15 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0067] Example 5
[0068] A method for preparing modified aerogel powder comprises the following steps:
[0069] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 2°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 14 hours after the addition is complete, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.5; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 0.7:1;
[0070] (2) Dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation reaction to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain modified polyamic acid powder; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:0.5; the dianhydride monomer is selected from pyromellitic dianhydride; the diamine monomer is selected from 4,4'-diaminodiphenylmethane; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1.02; and the organic solvent is selected from dimethylacetamide;
[0071] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.6;
[0072] (4) adding the amino carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the amino carbon nanotubes is 1:0.3;
[0073] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0074] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 14 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0075] Example 6
[0076] A method for preparing modified aerogel powder comprises the following steps:
[0077] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 4°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 20 hours after the addition is completed, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.6; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 0.9:1;
[0078] (2) Dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation reaction to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain modified polyamic acid powder; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:0.5; the dianhydride monomer is selected from 3,3`,4,4`-biphenyltetracarboxylic dianhydride and 3,3',4,4'-diphenylethertetracarboxylic dianhydride, and the molar ratio of the two is 1:1; the diamine monomer is selected from 4,4`-diaminodiphenyl ether; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1; the organic solvent is dimethylacetamide;
[0079] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.7;
[0080] (4) adding the amino carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the amino carbon nanotubes is 1:0.4;
[0081] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0082] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 15 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0083] Example 7
[0084] A method for preparing modified aerogel powder comprises the following steps:
[0085] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 2°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 16 hours after the addition is completed, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.6; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 0.8:1;
[0086] (2) Dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation reaction to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain modified polyamic acid powder; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:0.5; the dianhydride monomer is selected from 3,3`,4,4`-biphenyltetracarboxylic dianhydride; the diamine monomer is selected from 4,4`-diaminodiphenyl ether; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1.01; and the organic solvent is selected from dimethylacetamide;
[0087] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.5;
[0088] (4) adding the amino carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the amino carbon nanotubes is 1:0.3;
[0089] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0090] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 15 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0091] Example 8
[0092] A method for preparing modified aerogel powder comprises the following steps:
[0093] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 2°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 16 hours after the addition is completed, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.6; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 0.8:1;
[0094] (2) Dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation reaction to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain modified polyamic acid powder; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:0.5; the dianhydride monomer is selected from 3,3`,4,4`-biphenyltetracarboxylic dianhydride; the diamine monomer is selected from 4,4`-diaminodiphenyl ether; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1.01; and the organic solvent is selected from dimethylacetamide;
[0095] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.5;
[0096] (4) adding the amino carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the amino carbon nanotubes is 1:0.1;
[0097] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0098] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 15 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0099] Example 9
[0100] A method for preparing modified aerogel powder comprises the following steps:
[0101] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 2°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 16 hours after the addition is completed, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.6; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 0.8:1;
[0102] (2) Dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation reaction to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain modified polyamic acid powder; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:0.5; the dianhydride monomer is selected from 3,3`,4,4`-biphenyltetracarboxylic dianhydride; the diamine monomer is selected from 4,4`-diaminodiphenyl ether; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1.01; and the organic solvent is selected from dimethylacetamide;
[0103] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.5;
[0104] (4) adding the amino carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the amino carbon nanotubes is 1:0.6;
[0105] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0106] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 15 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0107] Comparative Example 1
[0108] A method for preparing modified aerogel powder comprises the following steps:
[0109] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 2°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 16 hours after the addition is completed, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.6; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 0.8:1;
[0110] (2) Dispersing dianhydride monomer, diamine monomer, polyaniline-modified nickel oxide nanoparticles and amino-modified carbon nanotubes in an organic solvent for polycondensation reaction to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain modified polyamic acid powder; the mass ratio of the sum of the dianhydride monomer and the diamine monomer to the polyaniline-modified nickel oxide nanoparticles and the amino-modified carbon nanotubes is 1:0.5:0.3; the dianhydride monomer is selected from 3,3`,4,4`-biphenyltetracarboxylic dianhydride; the diamine monomer is selected from 4,4`-diaminodiphenyl ether; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1.01; and the organic solvent is selected from dimethylacetamide;
[0111] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.5;
[0112] (4) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0113] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 15 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0114] Comparative Example 2
[0115] A method for preparing modified aerogel powder comprises the following steps:
[0116] (1) Dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 2°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and continuing stirring for 16 hours after the addition is completed, to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; filtering, washing, and drying to obtain polyaniline-modified nickel oxide nanoparticles; the particle size of the nickel oxide nanoparticles is 80 nm; the mass ratio of the nickel oxide nanoparticles to the aniline monomer is 1:0.6; the molar ratio of ammonium persulfate to the aniline monomer in the ammonium persulfate aqueous solution is 0.8:1;
[0117] (2) dispersing the dianhydride monomer and the diamine monomer in an organic solvent respectively for polycondensation to prepare a polyamic acid mixed solution; dropping the polyamic acid mixed solution into water for precipitation, filtering, washing and drying to obtain a modified polyamic acid powder; the dianhydride monomer is selected from 3,3',4,4'-biphenyltetracarboxylic dianhydride; the diamine monomer is selected from 4,4'-diaminodiphenyl ether; the molar ratio of the dianhydride monomer to the diamine monomer is 1:1.01; and the organic solvent is selected from dimethylacetamide;
[0118] (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelation; the organic base is triethylamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:0.5;
[0119] (4) adding aminated carbon nanotubes and polyaniline-modified nickel oxide nanoparticles into polyamic acid hydrogel and stirring evenly to obtain modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles and aminated carbon nanotubes is 1:0.5:0.3;
[0120] (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
[0121] A 3D printing polyurethane material comprises the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 15 parts of electromagnetic shielding aid; 2 parts of zinc stearate; the electromagnetic shielding aid is the modified aerogel powder prepared above.
[0122] Comparative Example 3
[0123] The preparation process and raw materials are basically the same as those in Example 7, except that the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass ratio of the polyaniline-modified nickel oxide nanoparticles is 1:0.2.
[0124] Comparative Example 4
[0125] The preparation process and raw materials are basically the same as those in Example 7, except that the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the polyaniline-modified nickel oxide nanoparticles is 1:1.
[0126] The polyurethane materials in the above embodiments and comparative examples were printed into strips, and the tensile properties of the strips were tested with reference to GB / T528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, and the electromagnetic shielding performance was tested using a shielding effectiveness meter.
[0127]
[0128] From Table 1 and Figure 3-5 It can be seen that the present invention introduces polyaniline-coated nickel oxide and amino-modified carbon nanotubes into polyimide aerogel powder to construct a polymer-based electromagnetic shielding composite material with a multiphase structure, thereby improving the electromagnetic shielding performance and mechanical properties of the 3D printed polyurethane material.
[0129] Figure 1 and Figure 2This is an electron microscope image of polyaniline-modified nickel oxide nanoparticles prepared in Example 7. It can be seen from the figure that polyaniline has been successfully coated on the surface of nickel oxide particles. The polyaniline-coated nickel oxide inside the gel can not only play the role of magnetic loss of nickel oxide magnetic powder, but also play the role of conductive filler after being coated and modified by polyaniline, so that the carbon nanotubes inside the gel and on the surface of the gel form a continuous conductive network, thereby improving the electromagnetic shielding performance of the aerogel powder in polyurethane. In Comparative Example 1, amino carbon nanotubes are added during the synthesis of polyimide, resulting in carbon nanotubes inside the hydrogel, and carbon nanotube structures cannot be formed on the surface of the aerogel. When used as a polyurethane electromagnetic shielding aid, they cannot contact each other to form a conductive network, which reduces the shielding effectiveness. In Comparative Example 2, amino carbon nanotubes and polyaniline-modified nickel oxide nanoparticles are added to the polyamic acid hydrogel, and a conductive channel cannot be formed inside the hydrogel. When used as a polyurethane electromagnetic shielding aid, they still cannot contact each other to form a conductive network. As an external modifier of aerogel, carbon nanotubes not only improve the compatibility of aerogel and polyurethane, but also play a role in conducting electricity and taking into account multiple reflections. Comparative Examples 3-4 show that when the amount of polyaniline-modified nickel oxide nanoparticles is small, a conductive network cannot be formed, and the absorption loss effect is reduced; when the amount of polyaniline-modified nickel oxide nanoparticles is too large, the honeycomb structure of the polyimide aerogel will be destroyed, causing pore damage, and multiple reflections cannot be formed to improve the absorption loss effect of the polyurethane material.
Claims
1. A method for preparing modified aerogel powder, characterized in that: The following steps are involved: (1) dispersing nickel oxide nanoparticles in deionized water, and adding aniline monomer dropwise at a low temperature of 0-5°C; adding ammonium persulfate aqueous solution dropwise under stirring conditions, and after the addition is completed, continuing to stir for 10-24 hours to obtain a polyaniline-modified nickel oxide nanoparticle dispersion; After filtering, washing and drying, polyaniline-modified nickel oxide nanoparticles are obtained; the mass ratio of nickel oxide nanoparticles to aniline monomer is 1:(0.4-0.8); (2) dispersing dianhydride monomer, diamine monomer and polyaniline-modified nickel oxide nanoparticles in an organic solvent for polycondensation to prepare a polyamic acid mixed solution; The polyamic acid mixed solution is dropped into water for precipitation, and the modified polyamic acid powder is obtained by filtering, washing and drying; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass ratio of the polyaniline-modified nickel oxide nanoparticles is 1: (0.4-0.6); (3) dispersing the modified polyamic acid powder in deionized water, adding an organic base, stirring evenly, and preparing a polyamic acid hydrogel through sol-gelization; (4) adding the aminated carbon nanotubes into the polyamic acid hydrogel and stirring evenly to obtain the modified polyamic acid hydrogel; the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the aminated carbon nanotubes is 1:(0.1-0.6); (5) The modified polyamic acid hydrogel is freeze-dried, thermally imidized, and crushed to obtain modified aerogel powder.
2. The method for preparing a modified aerogel powder according to claim 1, characterized in that: In step (1), the particle size of the nickel oxide nanoparticles is 40-100 nm.
3. The method for preparing a modified aerogel powder according to claim 1, characterized in that: In step (1), the molar ratio of ammonium persulfate to aniline monomer in the ammonium persulfate aqueous solution is (0.5-1):
1.
4. The method for preparing a modified aerogel powder according to claim 1, characterized in that: In step (2), the dianhydride monomer is selected from at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, and hexafluoro dianhydride; and the diamine monomer is selected from at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine, and 4,4'-diaminodiphenylmethane.
5. The method for preparing a modified aerogel powder according to claim 1, characterized in that: In step (2), the molar ratio of the dianhydride monomer to the diamine monomer is 1:(0.95-1.05); and the organic solvent is selected from at least one of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide.
6. The method for preparing a modified aerogel powder according to claim 1, characterized in that: In step (3), the organic base is at least one of triethylamine, tripropylamine, quinoline and triethylenediamine; and the mass ratio of the modified polyamic acid powder to the organic base is 1:(0.3-0.7).
7. The method for preparing a modified aerogel powder according to claim 1, characterized in that: In step (4), the mass ratio of the sum of the mass of the dianhydride monomer and the diamine monomer to the mass of the amino-modified carbon nanotubes is 1:(0.2-0.4).
8. A modified aerogel powder, characterized in that: The modified aerogel powder is prepared by the preparation method of any one of claims 1 to 7.
9. An application of the modified aerogel powder as claimed in claim 8, characterized in that: Modified aerogel powder is used in the field of 3D printing polyurethane materials.
10. A 3D printing polyurethane material, characterized in that: Contains the following components in parts by weight: 100 parts of thermoplastic polyurethane elastomer; 10-20 parts of electromagnetic shielding aid; 1-3 parts of lubricant; the electromagnetic shielding aid is the modified aerogel powder according to claim 8.
